A Case Report of Scapular Hemangioma with Kasabach–Merritt Syndrome: An Insight into Various Treatment Strategies with Review of Literature - Rajesh Bahadur Singh; Nitesh Joshi; Saravana Kumar Jagannathan; Raghawesh Ranjan; Zachariah Chowdhury; Paramita Rudra Pal (Indian Journal of Medical and Paediatric Oncology)
Hemangiomas are common tumors, accounting for 4 to 5% of all benign tumors in infancy and childhood. While they typically occur superficially, their presence in bone is extremely rare. This case report involves an 8-year-old female patient with a left scapular hemangioma, thrombocytopenia, and consumptive coagulopathy (Kasabach–Merritt syndrome). The patient presented with a slow-growing osseous lump in the left scapular region over 3 years. Magnetic resonance imaging revealed an expansile lytic lesion originating from the left scapula, with a large soft tissue component, areas of hemorrhage, necrosis, and bony destruction. A preoperative biopsy suggested hemangioma. During evaluation, the patient was found to have a low platelet count and consumptive coagulopathy, leading to a diagnosis of Kasabach–Merritt syndrome. The patient was managed with multimodal drug therapy. Due to the large size and progression of the lesion, a total scapulectomy was performed. Postoperatively, blood parameters normalized. Final histopathology confirmed a cavernous hemangioma. No recurrence or derangement in the coagulation profile was observed at the 6-month follow-up through clinical and X-ray examinations. This report is presented due to its exceptional rarity.